2019
DOI: 10.1093/cid/ciz409
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prescribing and Respiratory Viral Testing for Acute Upper Respiratory Infections Among Adult Patients at an Ambulatory Cancer Center

Abstract: Background. Outpatient antibiotic prescribing for acute upper respiratory infections (URIs) is a high-priority target for antimicrobial stewardship that has not been described for cancer patients.Methods. We conducted a retrospective cohort study of adult patients at an ambulatory cancer center with URI diagnoses from 1 October 2015 to 30 September 2016. We obtained antimicrobial prescribing, respiratory viral testing, and other clinical data at first encounter for the URI through day 14. We used generalized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…One strategy to improve prescribing has been the development and implementation of rapid diagnostic tests (RDTs) for RTIs based on the belief that if providers have accurate diagnoses quickly, it will improve prescribing [ 5 ]. Prior research by our team has shown that RDT use is low and clinical utility and impact on prescribing is varied [ 22 ], consistent with other reports [ 23 – 25 ]. In another study, providers in U.S. family medicine clinics had mixed attitudes about RDTs, citing inaccuracy, over-reliance on tests and costs as barriers to use [ 26 ].…”
Section: Introductionsupporting
confidence: 87%
“…One strategy to improve prescribing has been the development and implementation of rapid diagnostic tests (RDTs) for RTIs based on the belief that if providers have accurate diagnoses quickly, it will improve prescribing [ 5 ]. Prior research by our team has shown that RDT use is low and clinical utility and impact on prescribing is varied [ 22 ], consistent with other reports [ 23 – 25 ]. In another study, providers in U.S. family medicine clinics had mixed attitudes about RDTs, citing inaccuracy, over-reliance on tests and costs as barriers to use [ 26 ].…”
Section: Introductionsupporting
confidence: 87%
“…vs 1 h after sample collection Yes (results were reported and explained to physicians via telephone, text message or face-to-face) Shorter duration of intravenous antibiotics. More de-escalation within 72 h and between 72 h and 7 d [ 31 ] Adults in ambulatory cancer center Not applicable In-house MRVP, FilmArray respiratory Panel (Biofire, Utah, USA), Inlfuenza PCR (Cepheid) Retrospective cohort study About 24 h Not specified Viral testing on day 0 was associated with lower risk of antibiotic prescribing, though collinearity between viral testing and clinical service limited the ability to separate these effects on prescribing B. Antiviral therapy [ 8 ] Adults and children in ED during influenza season Not applicable FilmArray respiratory Panel (Biofire, Utah, USA) Prospective interventional Not specified Not specified (results communicated as soon as possible) More appropriate prescription of oseltamivir [ 12 ] Adults in tertiary care referral centre Not applicable DFA and MRVP (not specified) Retrospective observational cohort Not specified Not specified Positive sample associated with more antiviral use [ 14 ] Adults admitted for respiratory tract infection in tertiary care hospital Not applicable In-house MRVP Prospective, non-randomized 6–24 h Not specified (results communicated by phone/electronically) Influenza virus positivity was associated with appropriate antiviral management; positivity for viruses other than influenza was not correlated with significantly different outcomes [ 16 ] Adults in ED and inpatients during influenza season with ILI Not applicable …”
Section: Resultsmentioning
confidence: 99%
“…15 Recent studies assessing the impact of a viral diagnosis on antimicrobial management in hospitalized adults remain inconclusive or present a wide range of designs with mixed results. [16][17][18][19][20][21][22][23][24][25] Furthermore, influenza and RSV illness severity patterns are not necessarily associated with bacterial coinfections (eg, in older patients and/or patients with comorbidities). A positive viral diagnosis can therefore help clinicians to decide whether to withhold or discontinue antibiotic treatment based on patient medical history, clinical presentation, and available bacterial investigations results.…”
Section: Discussionmentioning
confidence: 99%